Who do you blame in local finance? An analysis of municipal financing in Italy - Massimo Bordignon; Santino Piazza (Center for Economic Studies and ifo Institute (CESifo), 2010)
A 1999 reform allowed Italian Mayors to partially substitute a more accountable source of tax revenue (the property tax) with a less transparent one (a surcharge on the personal income tax). Theoretical analysis suggests this should give incompetent Mayors a less costly way to hide themselves, so allowing them to be more easily re-elected. An empirical analysis on Piedmont municipalities confirms these hypotheses.
Keywords: H71; H77; D78; 330; partial decentralization; fiscal federalism; transparency; political behavior; Gemeindesteuer; Steuerpolitik; Public Choice; Finanzföderalismus; Theorie; Italien